Effects of Pyrrhotite on the Combustion Behavior and the Kinetic Mechanism of Pyrite-Pyrrhotite Mixture Powders in the Air - Changshun Tian; Yunzhang Rao; Gang Su; Tao Huang (International Journal of Chemical Engineering)
In this study, we performed a comparative analysis of the combustion behavior of pyrite, pyrrhotite, and pyrite-pyrrhotite mixture (mixed mineral) powders in an air atmosphere. To study the influence of the pyrrhotite content in mixed mineral powders on the combustion behavior in the air, thermogravimetric mass spectrometry, X-ray diffraction analysis, and scanning electron microscopy were employed. The results indicated that pyrrhotite lead to a weight gain in the mixed minerals during the combustion process. Pyrrhotite particles are more easily adsorbed on the surface of pyrite particles during mixed mineral combustion due to their strong ability to absorb oxygen, which accelerates pyrite combustion. The weight loss of mixed minerals decreased during the combustion process with increasing pyrrhotite content, resulting from pyrite encapsulation by agglomerated and sintered pyrrhotite during combustion. The calculated kinetic parameters and phase analysis results suggested that pyrite combustion is consistent with the shrinking core mechanism, and in the combustion process, the irregular pyrite particle shrank into a spherical particle; the combustion products of pyrrhotite grew in a layer-by-layer manner. Pyrrhotite combustion corresponded to the three-dimensional diffusion mechanism, and mixed mineral combustion was dominated by the shrinking core mechanism and supplemented by the three-dimensional diffusion mechanism. SO2, as the main combustion product, was continuously generated and volatilized in the reaction, signifying that the combustion reaction of pyrite is a two-phase reaction involving gas and solid.